Zinc-Silver, Zinc-Palladium, and Zinc-Gold as Bimetallic Systems for Carbon Tetrachloride Dechlorination in Water - T. N. Boronina; L. Dieken; I. Lagadic; K. J. Klabunde (Journal of Hazardous Substance Research, 1998)
Doping of zinc with silver, palladium, and gold was found to increase reactivity towards carbon tetrachloride in water. Commercial zinc dust, cryochemically prepared zinc metal particles (SMAD nanoparticles), and zinc dust pressed into pellets (mechanically activated zinc) were employed. Reduction products detected were methane, ethylene, acetylene, and other hydrocarbons along with products of partial dechlorination such as chloroform, methylene chloride, and methyl chloride. Dichloroethylenes (DCEs) and long-term reactions traces of trichloroethylene (TCE) were also detected. The use of zinc dust doped with palladium, gold, and silver resulted in 4-10 fold increases in carbon tetrachloride degradation rate and conversion into methane. Up to 30% of carbon tetrachloride was converted into methane by the Zn dust / 2 mol % Ag bimetallic system after the first six hours of reaction. Doping of activated forms of zinc, both cryoparticle and pellets, caused a further increase in methane formation and decrease in the concentration of methylene chloride. The data show that bimetallic enhancement with Pd, Ag, Au, as well as cryo and mechanical activation of zinc, enhances the metal surface reactivity and changes the priority of reaction pathways such that fully reduced products are favored. The “non-catalytic” gold metal was especially effective and this suggests that electron transfer, not catalytic hydrogenation, is rate determining.
Keywords: zinc; bimetallic; silver; palladium; gold; carbon tetrachloride; echlorination; water